Genome-Wide Association Study in Pigmentation as One of Skin Aging Characteristics - Farah Shabihah; Rafika Indah Paramita (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
Skin aging is a physiological process marked by changes in the skin's structure, giving rise to the characteristics of skin aging, such as pigmentation. Genome-Wide Association Studies (GWAS) identify genetic profiles that play a role in skin aging characteristics such as pigmentation. This study aimed to gather information about candidate SNPs and genes related to pigmentation characteristics of skin aging across different populations. We systematically searched relevant articles published in PubMed and ProQuest in the last ten years. Out of 212 articles screened, seven studies pertinent to our research are included in the analysis. Results indicated that in European and East Asian populations, several gene candidates such as IRF4, MC1R, ASIP, BNC2, PPARGC1B, RAB11FIP2, and CYP1A associated with SNPs that are known to have functions related to skin aging. However, further comprehensive analysis is needed to understand the functional correlation between SNP or gene candidates and pigmentation. In addition, the diversity of the subjects in the GWAS is still concerning. The future comprehensive analysis of GWAS, which involves underrepresented ones, is needed to broaden the knowledge of skin aging mechanisms across different populations.